Transforming Education: Lessons from the United States, Finland, South Korea, Brazil and Chile - Salazar Trujillo, Boris; Ordóñez, Luis Aurelio (Sociedad y Economía, 2016)
Although there is no a definitive method to appraise long-run educational reforms or policies,we claim that it is possible to find a set of regularities concerning the dynamics ofeducational reforms so as to assess their flexibility, transformational power, coherenceand capacity to mobilize the highest amount of social, human, intellectual, economicand cooperative resources. We found that successful and deeply transformational reformshave been the product of human action and not of human design, and that flexibility,social cohesion, community involvement and the adoption of complex adaptivesystems are the foundations for successful and enduring educational reform. Finland isa good example of the first type, Chile and Korea of failed reforms. and the United Statesis a special case, since it has managed to maintain its advantage in higher education,despite the weakness of their basic education.